Q. 124.0( 135 Votes )

Prove that sin<su

Answer :

To Prove: sin2 6x – sin2 4x = sin 2x sin 10x
Proof:

RHS = sin 2x sin 10x

LHS = sin2 6x – sin24x

we know that,

 [a2 – b2 = (a – b)(a + b)]

LHS = (sin 6x – sin 4x) (sin 6x + sin 4x)




Rearranging we get


LHS = (2 × sin x × cos x)(2 × sin 5x × cos 5x)


LHS = sin 2x sin 10x [ 2sin A cos A = sin 2A]


LHS = RHS


Hence, proved

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

If A + B + C = π,RS Aggarwal - Mathematics

If A + B + C = π,RS Aggarwal - Mathematics